ONCOPLASTIC SURGERY AND IMMEDIATE BREAST RECONSTRUCTION IN BREAST CANCER PATIENTS: SATISFACTION AND QUALITY OF LIFE EVALUATION - Giorgi, Lucimara Priscila Campos Veras; Dutra, Adriana Haack de Arruda (Mastology, 2019)
Objective: Oncoplastic surgery and breast reconstruction represent an advance in breast cancer surgeries, combining oncologic resection with plastic surgery techniques, and enabling optimal cancer treatment, good esthetic results, and improvement in patients’ quality of life. The objective of this study was to evaluate the satisfaction and quality of life of patients submitted to surgical treatment of breast cancer through oncoplastic surgery and breast reconstruction techniques. Methodology: Cross-sectional study with women undergoing surgical treatment of breast cancer through oncoplastic and/or breast reconstruction techniques, treated in the mastology center of the Federal District, from December 2016 to May 2017. The research instrument employed to assess satisfaction and quality of life was BREAST-Q. Data analysis adopted Student’s t-test or the Mann-Whitney test and simple linear regression to evaluate the relationship between age and the outcome investigated. Results: The final sample consisted of 15 women who met the eligibility criteria. The overall mean BREAST-Q score was greater than 54.2 for satisfaction and quality of life indicators. For each year of age, the sexual well-being score increased 0.15 (p<0.02); the satisfaction with medical team score, 0.83 (p<0.02); and the care satisfaction score, 0.23 (p<0.04). Conclusion: This study suggests that breast reconstruction improves satisfaction with breast appearance and quality of life in patients treated for breast cancer. Further longitudinal studies are necessary to elucidate the subject better.